COMPOSTING WASTE FROM AGRICULTURAL PRODUCTION OF COFFEE AND CORN AS A FORM OF COFFEE STRATEGY SOIL CONSERVATION: A CASE STUDY IN THE MUNICIPALITY DE LINHARES, ESPÍRITO SANTO (REMUNOM, 2024)
The population of Espírito Santo, currently around 3.8 million, is expected to reach 4.9 million by 2060. This population growth, combined with increased consumption, could lead to irreversible soil degradation, especially in essential crops such as coffee and corn. Instant coffee production generated US$108 million in 2022, representing 19.4% of Brazilian instant coffee exports, while corn production could grow by 33.8% in the 2022/23 harvest. However, these crops suffer from erosion caused by intensive agricultural practices, such as monoculture and excessive use of heavy machinery. Reusing agricultural waste through composting offers a sustainable solution, improving the physical, chemical and biological characteristics of the soil. The main objective of this study is to demonstrate how composting can be a financially accessible and effective technique for maintaining and improving soil in coffee and corn crops in Espírito Santo, aiming to mitigate the effects of erosion. To this end, a bibliographical survey was conducted on composting and its application in soil nutrition and preservation. Field research was also conducted on farms in Córrego Farias, Linhares, Espírito Santo, where improvements in the soil and increased productivity were observed after composting agricultural waste. Composting coffee and corn waste is an efficient practice for organic recycling and soil preservation. Coffee husks can control pests, conserve moisture and provide essential nutrients, while dried corn stalks act as mulch, adding nutrients and protecting the soil. Composting improves soil structure, increases water retention and provides nutrients, resulting in greater crop productivity. In addition, it reduces the costs of chemical fertilizers and attracts consumers who are aware of sustainable practices.